Manajemen Full Day School Dalam Meningkatkan Karakter Mandiri Siswa - Siddiq, Ahmad Jailani; Tosiman, Tosiman; Fahmi, Ach Syafiq; Inayati, Mahfida (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
This research aims to describe how full day school management improves the independent character of students at SDA Ummul Quro and SD Plus Nurul Hikmah. Which focuses on how to plan, organize, implement and evaluate full day school management in improving the independent character of students at SDA Ummul Quro and SD Plus Nurul Hikmah. Basically, an educational institution which consists of many human resources requires good management, because this has an impact on the progress of the school or educational institution. This research uses a qualitative approach with a descriptive type, data sources are obtained through interviews, observation and documentation. Several informants from SDA Ummul Quro and SD Plus Nurul Hikmah were the same, including; principal, head of Curriculum, teachers and students. Meanwhile, checking the validity of the data is carried out through extended participation, persistence, observation and triangulation. The results of this research show that; First, the two loci carry out planning using a meeting system involving school stakeholders. Second, the two loci carry out optimal organization or division of tasks with the same techniques, only there are differences in terms. Third, the implementation of full day school management in improving independent character is carried out by means of coordination meetings, program socialization, then starting. Fourth, program evaluation is also carried out at a maximum of two loci, but at SDA Ummul Quro with structured and unstructured evaluations, while at SD Plus Nurul Hikmah with weekly, monthly, semi-metered and annual evaluations